Optimal and heuristic algorithms for constructing interference-free multicast trees subject to delay and energy constraints on wireless mesh networks. (2016) - Yang, Wen-Lin
Due to the great concerns of environmental protection and the high rising of prices in oil, energy efficiency has become an important factor for designing network applications. In this paper, we study an optimisation problem which is concerned about how to construct an interference free multicast tree subject to delay and energy constraints on a multi-channel multi-radio wireless mesh network. Our objective is to maximise the number of mesh clients that can be included in the multicast tree. This problem is referred as the EDMRM problem. To solve it, we first propose an optimal algorithm on the basis of integer linear programming (ILP) for the EDMRM problem. Since the ILP-based method is only feasible for small-scale networks, we also provide a tabu-based heuristic algorithm for solving practical networks that consist of a large number of nodes. The experimental results show that our tabu-based heuristic can outperform the other previously proposed methods.